2020
DOI: 10.1002/ece3.5829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic connectivity of lionfish (Pterois volitans) in marine protected areas of the Gulf of Mexico and Caribbean Sea

Abstract: Lionfish (Pterois volitans) have rapidly invaded the tropical Atlantic and spread across the wider Caribbean in a relatively short period of time. Because of its high invasion capacity, we used it as a model to identify the connectivity among nine marine protected areas (MPAs) situated in four countries in the Gulf of Mexico and the Caribbean Sea. This study provides evidence of local genetic differentiation of P. volitans in the Gulf of Mexico and the Caribbean Sea. A total of 475 lionfish samples were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Genetic studies reveal that the lionfish population in Veracruz corresponds to the species P. volitans [5]. The first sighting of this species on the coast of Veracruz (western Gulf of Mexico) dates from 2011 in the VRS [6].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies reveal that the lionfish population in Veracruz corresponds to the species P. volitans [5]. The first sighting of this species on the coast of Veracruz (western Gulf of Mexico) dates from 2011 in the VRS [6].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, lionfish from The Bahamas and the Cayman Islands showed a higher occurrence of intersex (15%, Matthews and Morris 2019; 10%, Gardner 2012, respectively). The lower intersex in the gulf may be due to a genetic differentiation among lionfish populations (Guzmán-Méndez et al 2020) as suggested by Fogg et al (2017). However, the lionfish population in the north-eastern gulf has been reported to be panmictic with no sign of divergence (Pérez-Portela et al 2018).…”
Section: Discussionmentioning
confidence: 79%
“…Further, broader consideration of NNS risk in relation to marine spatial planning and marine connectivity is required. For example, the presence of artificial hard substrata associated with moorings, shipwrecks and offshore energy platforms may enhance marine connectivity (Tidbury et al, 2020), which facilitates NNS introduction, establishment and spread (Guzmán-Méndez et al, 2020).…”
Section: Conservation Management Considerationsmentioning
confidence: 99%